ABREK IN SOVIET CINEMA - Zel'nickaa, Rica Sotovna; Kazurova, Natal'a Valer'evna (History, Archeology and Ethnography of the Caucasus, 2025)
The visual art and narrative of the national cinema reveal the cultural, ethnic, religious and political attitudes of the state in which the authors work. The main research objective of this article is to analyse the role of Soviet cinema in changing the status of the abrek from a social outcast to the main fighter for revolutionary justice. Our materials are the Soviet films of different years Abrek Zaur/Son of the Mountains (1926) B. Mikhin, Zelimkhan (1929) O. Frelich, White Bashlyk (1974) V. Savelyev, Let's part while we are good (1991) V. Motyl. The methods of comparativism within the framework of visual anthropological approach will allow us to show the way of changing the meaning of the concept ‘abrek’. In the course of the study, we can conclude that early Soviet cinema works with the idea of forming the myth of the abrek as an opponent of the Russian Empire's policy. Anti-religious propaganda and opposition to the ideals of tsarism are created visual images that correspond to the ideology of the new authorities. In turn, the late Soviet cinema we see slow transformation of the image of the abrek. If in the late 1920s a cinematic hero present as a revolutionary and peasant protector who is not afraid of local elites, the tsar's prison and respected sheikhs then later one can observe the work of contemporary directors with the canon that had already been formed during the avant-garde period; gradually the atmosphere of the film rather than the hero himself changes. To summarise, we can conclude that films about abreks combined an ideological function and a commercial genre role in creating the image of the ‘correct’ abrek, turning him from a criminal rejected by his compatriots into the main fighter against the tsarist authorities and defender of the peasantry in the Caucasus.
Keywords: Cinema; Islam; Abrek; USSR; Caucasus